Psychoanalysis of Alice Garton Character as a Conservative Mother in Response to Helen and Chris Relationship in “Dear Nobody” by Berlie Doherty - Karin Maharani; Nungki Heriyati (Peneliti.net, 2023)
This study concerns on the character of conservative mother of Alice Garton in response to her daughter's love affair with her boyfriend, Chris in the novel “Dear Nobody” by Berlie Doherty. The researcher intends to discover the reasons why Alice Garton becomes very strict, super disciplined, overprotective, and overcare to Helen, her daughter, which made her reluctant to share her problems and hide her unexpected pregnancy from her. Moreover,this study is a descriptive qualitative research that uses the three personality aspects theory by Sigmund Freud as the psychoanalytic framework. The primary data source used in analyzing Alice Garton character is “Dear Nobody” novel by Berlie Doherty besides various reliable academic journals and books related to psychoanalysis as secondary data source. The data analysis technique employed is content analysis of the story. The result of this study will be presented in the narrative form which reveals that Alice's strict and conservatives personality according to the three personality aspects proposed by Freud is supergo for she behaves according to the norms and values that is accepted by society. The three reasons that Alice is a conservative are her standpoint, actions and beliefs.